Coexistence of Temporo-Occipital Polymicrogyria with Choroidal Fissure Cyst in a Case of Focal Onset Seizures - Kiran, M.; Karthik, A.; Lekshmi, L. V.; Nagarajan, K. (International Journal of Epilepsy, 2018)
Focal-onset seizures can be caused by underlying brain lesions including focal lesions such as granulomas, low-grade neoplasms, vascular lesions, or neuronal migration disorders. Polymicrogyria is a congenital abnormality of cortical formation occurring during embryonic life. Choroidal fissure cysts are either arachnoid or neuroepithelial cysts arising at the choroidal fissure, and mostly they are incidental findings having no significant clinical implications. Coexistence of both of these can lead to dilemma in the management decisions. We present a case of focal-onset seizures with an unreported coexistence of polymicrogyria with choroidal fissure cyst.
Keywords: polymicrogyria; choroidal fissure cyst; seizures; MRI